PENGARUH PDRB DAN PENGELUARAN PEMERINTAH PROVINSI PAPUA TERHADAP KEMISKINAN DI PAPUA - Marlina Marlina; Umaruddin Usman (LPPM UNIMAL, 2020)
The purpose of this study was to see the effect of GRDP and Expenditure on the Provincial Government of Papua on Poverty in Papua. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS). The data analysis method used in this study is multiple linear regression with the help of the program package eviews 10. The results showed that the GRDP variable has a negative effect on poverty, while the government expenditure variable does not negatively affect poverty, but together the GRDP variable and Government expenditure positively influences poverty in Papua and the magnitude of the effect of GRDP variable and government expenditure on poverty is 0.6966 (69.66%). Recommendations, it is expected that the local government of Papua can increase the GRDP which will be able to minimize poverty in Papua.Keywords: GRDP, Government Expenditure and Poverty